Perancangan Aplikasi Pembelajaran Bacaan Qiroah Irama Rost Berbasis Android (Studi Kasus MTS Al-Masykur 02) - Pujiyanti Purnamasari; Samsoni; Aprinia Handayani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Currently MTs Al-Masykur 02 has difficutly reading Qiroah prooerly and correctly, the difficulty of students getting facilities for reading and memorizing Qiroah from short letters, the need for innovation and overcoming the high number of students unable to read Qiroah with innovative processes and utilization in technology tools as a place of learning. This system is only limited to limiting users only to get Qiroah information and applying the waterfall method to the design of the Qiroah reading application. With this application I hope it can be useful for students of MTs Al-Masykur 02, and can make it easier for students to learn Qiroah as desired, and can help Muslims, especially Android users who have a high level of mobility to learn to read Qiroah properly and correctly.